A Literature Review : The Role of Corporate Boards in Enhancing Banks' Financial Performance - Khomidah, Tri Nurul; Lestari, Sri Widi (BALANCE: JOURNAL OF ISLAMIC ACCOUNTING, 2025)
This study explores the role of corporate boards in enhancing banks' financial performance by examining various board characteristics such as size, gender diversity, institutional ownership, board independence, audit committee structure, and financial expertise quality. It is a qualitative study that employs a literature review method that involves identifying, selecting, and synthesizing relevant journal articles to understand the key characteristics and impacts of corporate boards. The data consist of journal articles related to corporate boards, sourced from both Indonesian and international reputable journals. These articles were selected based on their relevance to the research topic. The literature review reveals that effective boards significantly contribute to improving bank profitability, primarily through tighter oversight, optimal risk management, and well-informed strategic decision-making. Gender diversity on boards also proves to enhance transparency and corporate governance, while the duality of CEO and Board Chair roles may reduce oversight effectiveness. Besides internal factors, the findings emphasize the importance of managing external risks, such as political and economic instability, to sustain bank performance. This study offers important implications for bank management and regulators to strengthen corporate governance by establishing competent and diverse boards to drive sustainable and stable financial performance in the banking sector.